The Q methodology in determining educational attitudes of some Philippine teachers a preliminary study. - Paik, Yong-Duck. ([Quezon City s.n.], 1972)
The aim of this study was to find out the applicability of Q methodology in the Philippine setting, as a preliminary study, in accordance with the method Kerlinger. If the results of this study agree with the results of Kerlinger's studies, then it would indicate that Q methodology is applicable for the study of individual attitudes in the Philippine setting.
Thesis (M. Ed.)--University of the Philippines.
Keywords: Teachers; Educational psychology; Philippines. University -- Faculty